Empowerment Of Disabled People In Wonogiri District In Making Shibori Ciprat Batik To Improve Social Welfare - Nadhiroh; Atik Nurfatmawati; Sugiyanto; Ardillah Agnaina Aulia (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
This article attempts to explore the results of the implementation of community service entitled Empowerment of Disabled People in Wonogiri District in Making Shibori Ciprat Batik to Improve Social Welfare. Several things behind this service include the need to make efforts to equalize access to friends with disabilities in Wonogiri Regency and maximize their potential in order to increase independence. The theory that is relevant to this empowerment is Critical Social Theory. This theory believes that society is characterized by historicity or experiences continuous change. The method used in service is Participatory Action Research (PAR). The efforts in this service are to meet the needs and solve the problems faced by disabled people in Wonogiri District in developing the ability to make shibori splash batik. This community service aims firstly, to empower disabled people in Wonogiri District in training in shibori ciprat batik to improve social welfare. Second, to examine the supporting and inhibiting factors for empowering disabled people in Wonogiri District in shibori ciprat batik training to improve social welfare. The results of the service show, firstly, that disabled people in Wonogiri District have increased their knowledge and ability to make shibori batik, splashed batik and can make a combination of the two, namely splashed shibori batik. Second, increasing knowledge about entrepreneurship and digital marketing through social media which was followed up by creating an IG @batik.shipatdiwo as a means of socialization and marketing. Third, the formation of the Batik Shipat Diwo Joint Business Group (KUBE) (Shibori Ciprat Difabel Wonogiri). The supporting factor for service is that the majority of disabled people have a high enthusiasm for development. The inhibiting factor for devotion is the inferior attitude of a small number of people with disabilities.